E-Test or Agar Dilution for Metronidazole Susceptibility Testing of Helicobacter pylori: Importance of the Prevalence of Metronidazole Resistance - Chen, Jinnan; Huang, Yu; Ding, Zhaohui; Liang, Xiao; Lu, Hong (Frontiers in Microbiology, 2022)
Background A number of studies have shown that E-test overestimated the presence of Helicobacter pylori (H. pylori) resistance compared to agar dilution. Objective The purpose of this study was to explore whether E-test could be an alternative for agar dilution to detect the metronidazole susceptibility of H. pylori. Method E-test and agar dilution were used to assess susceptibility of H. pylori to metronidazole, clarithromycin and levofloxacin in 281 clinical isolates obtained from China where resistance was high. Cohen kappa analysis, McNemar test, essential and categorical agreement analysis were performed for these two methods. Results Overall, the result of E-test showed similar prevalence of resistance rate to all antibiotics compared with agar dilution. The essential agreement (EA) of E-test method and agar dilution in the evaluation susceptibility of H. pylori to clarithromycin and levofloxacin were moderate, with 89.0% and 79.7% respectively, but only 45.9% for metronidazole. Results showed categorical agreement (CA) between E-test and agar dilution were 100% for both clarithromycin and levofloxacin. As for metronidazole, the CA was 98.7%, no major error was identified, and rate of very major error was 1.8%. Conclusion E-test can be an alternative method to detect the metronidazole susceptibility of H. pylori in regions where high-level resistance is common.